The interplay between insomnia, sleep aid use, and perceived stress: A cross-sectional study among medical students in Dammam, Saudi Arabia - Al-Johani, Wejdan M. (Acta Biomedica Atenei Parmensis, 2025)
Background and Aim: Sleep is essential for maintaining both physical and psychological health and for supporting cognitive processes. Insomnia is highly prevalent among medical students worldwide, primarily due to academic demands and lifestyle factors. This study assesses the prevalence and predictors of insomnia among medical students in Saudi Arabia and explores its association with perceived stress and sleep-aid use. Methods: A cross-sectional online survey was conducted among medical students in Dammam, Saudi Arabia. The questionnaire included sociodemographic data, the Insomnia Severity Index (ISI), the Perceived Stress Scale (PSS), and sleep-aid use. Data were analyzed using SPSS Statistics version 27, with a p-value < 0.05 considered statistically significant. Categorical variables were summarized as frequencies and percentages, and associations were examined using Pearson’s Chi-square, the Fisher–Freeman–Halton exact test, and Multiple linear regression analysis. Results: Of the 407 students who completed the survey, 53.6% were female. According to ISI scores, 26.0% had subthreshold insomnia, 18.7% had moderate insomnia, and 0.7% had severe insomnia. Stress levels were elevated, with 49.9% reporting moderate stress and 13.5% reporting high stress. Nearly 48.2% reported using sleep aids at some point. Significant associations were identified between insomnia and perceived stress, academic failure, lower monthly income, and sleep-aid use. Conclusion: Insomnia among medical students is associated with stress, demographic factors, and academic pressure. The high prevalence of insomnia and frequent sleep-aid use underscores the necessity for institutional support, sleep education, and enhanced mental health resources.